(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In recent years, the problem of stroke has become even more important due to the increase in childhood strokes. The relevance of studying this problem in children is due to the fact that, unlike an adult, a child who has had a stroke is forced to develop against the background of formed neurological complications, and many parents do not have the opportunity to meet the needs of such a child.